THE URGENCY OF A SYSTEM APPROACH IN PREVENTION CORRUPTION CRIME OF PROCUREMENT OF GOODS AND SERVICES (ROBERT KLITGAARD'S CDMA THEORY APPROACH ANALYSIS) - Danutirtho Satrio Pinandito (Jurnal Hukum Khaira Ummah, 2022)
The Corruption Prevention System in the field of procurement of goods and services has improved towards its ideal goal, namely values for money in every aspect of procurement. But there are still hidden criminogenic factors in the current system. This article aims to explain the system for preventing corruption in the procurement of goods and services based on Robert Klitgaard's CDMA theory approach. Secondary data in the form of Laws and Regulations related to the procurement of goods and services is elaborated with Robert Klitgaard's CDMA Theory, through a normative juridical approach. The analysis orientation uses the law and concept approach. The results found first: any loopholes indicated by the strengthening of discretion of officials with an interest in the procurement of goods and services need layered control in limiting their discretionary powers. Second: Monopoly variables in all stages of procurement of goods and services need to be watched out for if practice develops the fact that it is narrowed down to a single supplier and technical specifications that lead to a single supplier. Third: accountability can be strengthened by providing layered supervision, from internal and external sources of the goods and service procurement system.Keywords: Procurement of Goods and Services, Corruption, CDMA Theory